Analysis Of The Influence Of SBI Interest Rate, Exchange Value, Dow Jones Index And Gold Prices On Joint Stock Price Index In Indonesia Stock Exchange - Riko Setya Wijaya; Marseto; Emilda Widiani Sabrina (Institute of Computer Science (IOCS), 2022)
The capital market is one of the drivers of a country's economy, the condition of a country's capital market is strongly influenced by various factors, namely internal and external macroeconomic conditions that affect the country. , the Dow Jones Index and the price of gold against the Stock Price Index (JCI), during the 2018 observation period quarter I - 2021 Quarter IV, either partially or simultaneously. The data used in the form of secondary data obtained through the website of Bank Indonesia and idx. The data analysis method used is multiple linear regression analysis with a significance level of 0.05. The conclusion of this study is that in the period, the exchange rate of the Rupiah against the United States Dollar, the Dow Jones Index and the gold price partially had a significant effect on the JCI. Meanwhile, the BI interest rate has no effect on the JCI. In addition, it was found that the R-square value was 87.7%. This means that 87.7% of all observations show that the independent variable is able to explain the variation of the dependent variable, the remaining 12.3% (obtained from 100% - 87.7%) is influenced by other factors that are not visible in the model or the error..